The effects of the treatment forms in immune thrombocytopenic purpura on thrombocyte volume parameters - Akarsu, Saadet; Bozda?, Şenol; Kurt, Abdullah; Çitak Kurt, A. Neşe; Yilmaz, Erdal (My University, 2006)
Immune thrombocytopenic purpura (ITP) is a clinical case causing changes in volume parameters, as well as in the number of thrombocytes. In this study, we aimed to determine thrombocyte volume parameters (mean platelet volume, MPV; platelet distribution width, PDW) patients with acute ITP and the effects on them of different treatments. Of the 56 patients, 68% were given IV methylprednisolone (MP, Group 1), 16% IVIG (Group 2), and 16% MP in conjunction with IVIG (MP+IVIG, Group 3). Prior to and after therapy MPV values, in Group 1 were 7.3-8.2 (p<0.05), in Group 2 7.4-7.7 (p>0.05) and in Group 3 5.7-7.8 fl (p>0.05). Prior to and after therapy PDW values in Group 1 were 13.7-15.1 (p<0.05), in Group 2 11.0-13.0 (p>0.05), and in Group 3 12.8-14.5 fl (p>0.05). If MPV and PDW values are followed carefully, it is possible to estimate a bleeding risk and response to treatment prior to the thrombocyte number. An ideal treatment form can be determined. In our patients, MP treatment was regarded as more successful than the others.
İmmün trombositopenik purpurada tedavi şekillerinin trombosit hacim parametreleri üzerine etkisi
Keywords: Immune thrombocytopenic purpura; Mean platelet volume; Platelet distribution width; Platelet volume parameters; Treatment